Nutritive Value of Coffee Husk Fermented with Pleurotus ostreatus as Ruminant Feed - I Badarina; D Evvyernie; T Toharmat; E N Herliyana; I K Darusman (Faculty of Animal Science, Bogor Agricultural University, 2013)
Coffee husks is an abundant crop residue but the content of anti nutritional substances such as caffeine, tannin, and lignin limit its utilization as feed ingredients. Higher fungi such as Pleurotus ostreatus have the ability to biotransform lignocellulosic materials through their extracellular enzyme activities. This study was carried out to assess the effect of solid state fermentation by using P. ostreatus on nutrient composition of coffee husk and to evaluate its potency as ruminant feed in vitro. The in vitro experiment was conducted to determine fermentability of treated coffee husk. The usage rate of fermented coffee husk was mimicked feeding level to mid lactation dairy cows; 0%, 10%, 20%, 30%, and 40% (R0 to R4). Fermentation of coffee husk by P. ostreatus increased its protein, from 10.36% to 12.14%, and cellulose, from 19.51% to 24.80%, and decreased its lignin, from 65.42% to 45.04%, tannin from 1.02% to 0.18%, and caffeine, from 1.39% to 0.20%, concentrations. There were no differences in ruminal pH and N-ammonia production but volatile fatty acid production and dry matter digestibility decreased as the fermented coffee husk level increased. The ruminal protozoa population in fermented coffee husk diets was lower than the control diets (P<0.05). In conclusion, it is possible to use 20% of fermented coffee husk in the ration.